PERAN GURU DALAM MENINGKATKAN PRESTASI SISWA DI SEKOLAH MENENGAH ATAS NEGERI 12 PEKANBARU - Siregar, Nico Alpino; ", Basri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research have a title role of teacher in increases student accomplishment atprivate senior high school 12 Pekanbaru. Based on problem background so thisresearch formulation: is form teacher role in increase student accomplishment atprivate senior high school 12 Pekanbaru? and everything student accomplishment atprivate senior high school 12 Pekanbaru?. This research aims to detect to what teacherrole form in increase student accomplishment at private senior high school 12Pekanbaru and everything student accomplishment at private senior high school 12Pekanbaru. Research conduct at SMAN 12 Pekanbaru. this research time is during 6months commencing from January 2015 until June 2015 or since proposal continuedwith writing skripsi up to scholar test. Population is object or subjek that present at oneparticular area and fulfil certain terms related to research problem Riduwan (2005:11). Population in this research teacher SMAN 12 Pekanbaru that numbers as much as65 students and entire to made sample. This research has descriptive so data analysistechnique that is used depiction technique with words or sentence and separate followthe category to get data conclusion and get accurate conclusion in this research. Basedon data about teacher role in increase student accomplishment at private senior highschool 12 Pekanbaru inferential: 1) teacher role in increase student accomplishment atprivate senior high school 12 Pekanbaru with percentage 76% and belong to intocategory enough. Mean, has part good enough in increase student accomplishment atprivate senior high school 12 Pekanbaru. 2) Student effort to reaches accomplishmentat private senior high school 12 Pekanbaru with percentage 86% and belong to intogood category. Mean, student has done effort in increase accomplishment learn it atprivate senior high school 12 Pekanbaru well.Keyword: Teacher role, student accomplishment SMA